Effects of Tinnitus Sound Therapy Determined Using Subjective Measurements - Jin, In-Ki; Choi, Soon-Je; Yoo, Jeeun; Jeong, Seungyeop; Heo, Sohee; Oh, Hongyeop (Journal of the American Academy of Audiology, 2021)
Background Sound therapy is generally considered as an effective method for relieving tinnitus. There have been various reports on the effects of tinnitus interventions involving sound therapy as a component; however, there have been only a small number of reports on the effects of sound therapy itself on tinnitus.Purpose The aim of the study is to elucidate whether sound therapy significantly improves tinnitus as determined by subjective measurements.Research Design Prospective study involves within-subject (baseline, 3-month, 6-month) measurements.Study Sample This includes 16 adults with subjective and sensorineural tinnitus.Intervention Participants undertook sound therapy for 3 hours a day for 6 months. The level of stimulus for sound therapy was set to the mixing point of each participant. No counseling was provided.Data Collection and Analysis Participants rated the visual analog scale for loudness and annoyance using a numeric 0 to 100 point scale and completed the Korean version of the Tinnitus Primary Function Questionnaire at the baseline, 3-month, and 6-month time points.Results Sound therapy led to significant improvements of tinnitus in participants in all subjective measurements. Significant effects were found not only between the baseline and 3-month but also between the 3-month and 6-month follow-ups.Conclusion Results of the present study showed that the sound therapy alone led to significant improvements of tinnitus in participants as assessed by subjective measurements. To improve the effects of sound therapy, consistent sound therapy may be required for a certain period of time such as 3 hours a day over a 6-month period.
Keywords: tinnitus; sound therapy; subjective tinnitus